2021
DOI: 10.18295/squmj.2021.21.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Management of Totally Implantable Central Venous Access Ports in Cancer Patients at a University Hospital in Oman

Abstract: Objectives: Totally implantable central venous access ports (port-a-caths) are increasingly used for the safe administration of chemotherapy; however, their use is associated with complications. This study reviews patterns of complications, reasons for premature removal and the duration of the use of port-a-caths in patients receiving cancer treatment at Sultan Qaboos University Hospital (SQUH) and compares the infection rate with the literature and the researchers’ experiences. Methods: This retrospective fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Complications of IVAP often result in removal, prolonged hospital stay, intensive care unit admission, and death (30). Infection is the most common complication associated with IVAP (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications of IVAP often result in removal, prolonged hospital stay, intensive care unit admission, and death (30). Infection is the most common complication associated with IVAP (31).…”
Section: Discussionmentioning
confidence: 99%
“…Infection is the most common complication associated with IVAP (31). In particular, IVAP infection has a high morbidity rate and can result in early removal of IVAP (30). In addition, infections increase the length of hospital stay, morbidity, mortality, longterm antibiotic use, and costs (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies are necessary to determine the superiority of one technique or venous insertion site over another definitively. Although many studies in the literature have demonstrated the safety of chemotherapy ports, the majority of these procedures have been performed by interventional radiologists (26,2). Recent studies have indicated a shift in the healthcare landscape even for the non-tunneled vascular catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Over 50% of the patients underwent a single round of chemotherapy, with the remaining individuals opting for multiple lines of treatment delivered through the same port-a-cath. Notably, two patients abstained from receiving any cytotoxic chemotherapy [20]. For Skin A light-responsive, swiftly detachable microneedle (MN) patch designed to expediently transport drugloaded MNs to the skin, enabling recurrent administration of chemotherapy and photothermal therapy to superficial tumors through light activation.…”
Section: For Breast Cancermentioning
confidence: 99%
“…The MNs, composed of a PCL polymer containing photosensitive nanomaterials LaB6 (lanthanum hexaboride) serving as photothermal transducers and the anticancer drug doxorubicin (DOX), were employed for cancer treatment. [20] Techniques [14] • Three-Dimensional Printing (3D Printing) Three-dimensional (3D) printing, an additive manufacturing (AM) technique pioneered at the Massachusetts Institute of Technology in the 1990s, involves converting Computer-Aided Design (CAD) into a Stereo Lithography (STL) file. This STL file is then utilized by the 3D printer to manage material movement and deposition.…”
Section: For Breast Cancermentioning
confidence: 99%